THE MANAGEMENT OF SPENT CATALYST OF HYDROCONVERSION PROCESSES IN ASEAN REFINERIES - A.S. Nasution; E. Jasjfi (Scientific Contributions Oil and Gas, 2004)
Catalytic processing is a keystone of todayâ€™s petroleum refining. The catalytic processes applied in the potreleum industry are generally large scale. In todayâ€™s operating climate of increased attentiveness toward environmental and safety issues, spent catalyst management options have became an important consideration for refiners. A catalyst deactivation determines how it can be handled after it is discharged from the processing unit. The type of the catalyst and its condition (whether it is considered hazardous) often determines the disposal route selected. Because of the self-heating and leaching problems associated with spent hydrotreating catalyst,it is recommended that refiners ship their spent catalysts to what is called â€œtrue recyclesâ€. The U.S. Environmental Protection Agency (EPA), for example, is in the process of reevaluating the designation of spent hydroprocessing catalyst as an hazardous waste. Out of 3,837 MBPSD total crude oil currently processed in ASEAN (Brunai Darussalam, Indonesia, Malaysia, Philippenes, Singapore, Thailand, not including Vietnam, Laos and Myanmar) arround 61 percent volume is passed through catalytic processes (included hydroconversion processes 58 vol.%) to produce various fuel components such as gasoline and diesel oil. These hydroconversion processes use about 3,279 tons of catalyst with about 28 tons per day of spent catalyst. The present paper discusses briefly a survey on the management of spent catalyst of hydroconverion processes in ASEAN refineries and some aspects of catalyst poisoning of major hydroconversion processes in petroleum refinery. A survey on the management of spent catalyst from hydroconversion processes in ASEAN refineries is described in this paper.